2019
DOI: 10.1101/2019.12.11.871855
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early sexual dimorphism in the developing gut microbiome of northern elephant seals

Abstract: 34The gut microbiome is an integral part of a species' ecology, but we know little about how host characteristics 35 impact its development in wild populations. Here, we explored the role of such intrinsic factors in shaping the gut 36 microbiome of northern elephant seals during a critical developmental window of six weeks after weaning, when 37 the pups stay ashore without feeding. We show that the early-life gut microbiome is already substantially different 38 in male and female pups, even though males and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 93 publications
3
26
1
Order By: Relevance
“…Cluster 2 shows patterns similar to those observed in females. It seems that the microbial community diverges early in life based on sex as reported in northern elephant seal pups under a naturally controlled diet (Stoffel et al, 2020). Sexual dimorphism is a common mating strategy in otariids.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Cluster 2 shows patterns similar to those observed in females. It seems that the microbial community diverges early in life based on sex as reported in northern elephant seal pups under a naturally controlled diet (Stoffel et al, 2020). Sexual dimorphism is a common mating strategy in otariids.…”
Section: Discussionmentioning
confidence: 88%
“…For example, following its initial acquisition during birth and lactation, the microbiome is constantly modified by factors such as age, sex, and diet (Ley et al, 2008a, 2008b; Nicholson et al, 2012). Similar factors shaping the gut microbiome in terrestrial mammals influence that of marine mammals (Nelson et al, 2013; Pacheco‐Sandoval et al, 2019; Smith et al, 2013; Stoffel et al, 2020). However, studies have also shown substantial differences between marine and terrestrial mammal gut microbiomes, even when these two groups share a similar diet (e.g., herbivore, carnivore) (Bik et al, 2016; Nelson et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies investigating the relationship between GM alpha diversity and individual condition have shown mixed results, with both positive [23,31,77] and negative [32,33,78] relationships, as well the absence of an association [79,80] being identified across various wild and captive vertebrate host species. However, these studies often focus on early life stages, despite the fact that body mass can be an important predictor of fitness in adult individuals [63,81,82].…”
Section: Gut Microbiome Diversity and Body Conditionmentioning
confidence: 91%
“…The emergence of high-throughput sequencing technologies, in combination with the development of effective, non-invasive sampling techniques, has resulted in a recent proliferation of studies investigating the GM of wild animals. Several studies have demonstrated interspecific differences in GM characteristics [17][18][19], and also variation between groups [20][21][22] or individuals [23][24][25] within the same natural population. Most of these studies have focussed on investigating the drivers of intraspecific variation in the bacterial component of the GM, identifying a suite of environmental factors that can influence this, including habitat quality and dietary differences [24][25][26], as well as host-related traits, such as age, sex, and host genotype [23,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation